2021
DOI: 10.1016/j.immuni.2021.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Limited access to antigen drives generation of early B cell memory while restraining the plasmablast response

Abstract: Highlights d scRNA-seq reveals early divergence of PBs, GCBCs, and MBCs from the common precursor d Unlike PBs and GCBCs, eMBCs remain transcriptionally similar to the precursors d Cell cycle exit of eMBCs is driven by the decline in antigen availability d Provision of antigen excess drives generation of a new PB wave from eMBCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 89 publications
4
66
0
Order By: Relevance
“…5C, D ) [ 56 ]. On the other hand, clusters 2 and 3, in 4T1 and EMT6 respectively, had a similar transcriptional profile attributable to a proliferative B cell population, as confirmed by the expression of Mki67 and Mcm5 genes [ 39 , 57 ]. Similarly, cluster 4 and cluster 7, in 4T1 and EMT6 respectively, highly expressed Cd38 gene but not Mki67 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5C, D ) [ 56 ]. On the other hand, clusters 2 and 3, in 4T1 and EMT6 respectively, had a similar transcriptional profile attributable to a proliferative B cell population, as confirmed by the expression of Mki67 and Mcm5 genes [ 39 , 57 ]. Similarly, cluster 4 and cluster 7, in 4T1 and EMT6 respectively, highly expressed Cd38 gene but not Mki67 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also depending on the results and the expression of known gene markers the granularity was chosen accordingly (0.2 and 0.3 for Cd4 and Cd8 respectively in 4T1 cell line, 0.1 and 0.2 for B in the 4T1 and EMT6 cell line respectively, 0.4 for macrophages in EMT6 cell line). The sub-clusters cell assignment was performed only with manual curation by choosing a known set of genes from relevant studies that focus on the same cell populations [ 39 42 ] in similar mouse models and evaluating their expression in the sub-clusters.…”
Section: Methodsmentioning
confidence: 99%
“…Before entering the GC, activated B cells compete for follicular helper T (Tfh) cell help at the T-B border based on the amount of peptide-MHC class II (MHC-II) presented by the B cells to the Tfh cells. Hence, the success of B cells competing for early Tfh help depends on their frequency and their B cell receptor (BCR) affinity for antigens (14)(15)(16)(17). Rare B cells, such as broadly neutralizing antibody (bnAb) precursor B cells with low affinity (18), may be excluded from entering the GC at this early Tfh cell checkpoint.…”
Section: Positive Selection Of High-affinity Gc B Cellsmentioning
confidence: 99%
“…However, Price et al (37) demonstrated the feasibility to molecularly characterize ASC following intracellular staining for both antibody isotype as well as antibody specificity using tetramer constructs of antigens bound to fluorophore-conjugated streptavidin. Alternatively, early IgG-expressing ASC (IgG-ASC) often continue to bear their antibodies at the cell membrane, and surface staining for antibody isotype and antigen-specificity with tetramers offers a simpler method for isolating such IgG-ASC, though represents a restricted view of the whole IgG-ASC population (38,39). Flow cytometry is also a valuable tool for scouting potential novel markers of ASC subsets (40).…”
Section: Cytometry-based Assaysmentioning
confidence: 99%
“…Recent advances on ASC characterization using RNAseq, ATAC-seq and ChIP-seq have been reviewed elsewhere (86), as well as molecular mechanisms leading to plasma cell differentiation from the germinal center reaction (87). Glaros et al (38) highlight the capacity for scRNAseq to identify B cell subsets and observe shifts in differentiation, identifying antigen availability as a key regulator of the plasmablast response.…”
Section: Molecular Analysesmentioning
confidence: 99%